EXPLORING THE INFLUENCE OF PERCEIVED ACCESSIBILITY ON COMMUTER MODE CHOICE PREFERENCE IN THE CORRIDOR OF LRT JABODEBEK BEKASI LINE - Rivan Zhafira, Muhammad
This study aims to explore the relationship between perceived accessibility and commuter workers' transportation mode preferences, specifically in the new LRT Jabodebek transport corridor. This is undertaken because a deeper understanding of how perceived accessibility influences transportation mode choices can aid in more effective transportation planning that is responsive to user needs. The study compares the extent to which perceptions of accessibility explain actual accessibility and reduces perceived accessibility measured with Likert variables using principal component analysis (PCA). Mode choice preferences are constructed with stated preferences, and factors such as socio-demographics, travel characteristics, and the results of PCA on perceived accessibility are measured for their influence using multinomial logistic regression. The study findings show that although the physical distance to LRT stations can be objectively measured, individual perceptions of this distance vary. This understanding indicates that transportation planning should consider not only physical accessibility but also how users perceive this accessibility. The differentiation based on actual accessibility is also measured to influence the decision-making of travelers in choosing transportation modes. Several socio-demographic and travel factors are found to affect the preference for LRT and bus modes. Meanwhile, subjective aspects such as satisfaction with the transportation mode, travel time, and travel cost are found to influence transportation mode preferences.